Adjustment of corporate real estate during a period of significant business change - Cooke, Howard; Appel-Meulenbroek, Rianne; Arentze, Theo (International Journal of Strategic Property Management, 2019)
This paper seeks to understand whether the alignment process between business strategy and Corporate Real Estate (CRE) between 2007 and 2014 was dynamic. It investigated the financial data of 230 UK companies by means of a distributed time lag auto-regression model. The results show an increased commitment to CRE suggesting a reduced ability to dynamically align the portfolio. Evidence is found that CRE adjusts as turnover, profitability and employment numbers alter. However, measures of efficiency, effectiveness and productivity are not improving. The new business strategies of transient competitive advantage and blue oceans strategy require flexible resources, which require CRE to be capable of dynamic alignment. This study shows such flexibility does not yet exist in practice. Current theories of alignment should be reconsidered in light of the changing business environment. Without a dynamic alignment capability of CRE a company’s financial performance will be impaired.